METODE DISPROGRAMMING DALAM MENDESAIN PASAR IKAN DADAP - Fahmi Syafutra; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2021)
Geographically, Indonesia is an archipelago with a sea area larger than land, but unfortunately the potential of the coast has not been utilized properly. This is not an exception to Kampung Dadap, which is an area on the coast of the North Java coast that borders the Tangerang and DKI Jakarta Regencies. The majority of the people of Dadap Fishermen Village, who work as fishermen and roadside traders, do not have activity support facilities as a place for them to express their activities, so that their economic potential does not develop, making the fishermen's village appear to be a dead village due to lack of visitors. In responding to the problems that arise, this project aims to make the Fish Market a supporting facility for fishery activities that can attract visitors, which can improve the quality of life of the Dadap Fishermen Village community in dwelling, social and economic context. This project is aimed at all communities, especially around the Dadap Kosambi Fisherman Village area. With the modern market concept of